At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the equation [tex]\(-4x - 2 = x + 1\)[/tex], we need to isolate the variable [tex]\(x\)[/tex].
Let's go through the steps:
1. Move all terms involving [tex]\(x\)[/tex] to one side of the equation:
- Subtract [tex]\(x\)[/tex] from both sides to bring the [tex]\(x\)[/tex] terms together.
[tex]\[ -4x - x - 2 = 1 \][/tex]
2. Combine like terms:
- On the left-hand side, [tex]\(-4x - x\)[/tex] combines to [tex]\(-5x\)[/tex].
[tex]\[ -5x - 2 = 1 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term:
- Add 2 to both sides of the equation to move the constant term.
[tex]\[ -5x = 1 + 2 \][/tex]
- Simplify the right side.
[tex]\[ -5x = 3 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
- Divide both sides of the equation by [tex]\(-5\)[/tex] to solve for [tex]\(x\)[/tex].
[tex]\[ x = \frac{3}{-5} \][/tex]
- Simplify the fraction.
[tex]\[ x = -\frac{3}{5} \][/tex]
- Convert the fraction to a decimal.
[tex]\[ x = -0.6 \][/tex]
Therefore, the solution to the equation [tex]\(-4x - 2 = x + 1\)[/tex] is [tex]\(x = -0.6\)[/tex].
Let's go through the steps:
1. Move all terms involving [tex]\(x\)[/tex] to one side of the equation:
- Subtract [tex]\(x\)[/tex] from both sides to bring the [tex]\(x\)[/tex] terms together.
[tex]\[ -4x - x - 2 = 1 \][/tex]
2. Combine like terms:
- On the left-hand side, [tex]\(-4x - x\)[/tex] combines to [tex]\(-5x\)[/tex].
[tex]\[ -5x - 2 = 1 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term:
- Add 2 to both sides of the equation to move the constant term.
[tex]\[ -5x = 1 + 2 \][/tex]
- Simplify the right side.
[tex]\[ -5x = 3 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
- Divide both sides of the equation by [tex]\(-5\)[/tex] to solve for [tex]\(x\)[/tex].
[tex]\[ x = \frac{3}{-5} \][/tex]
- Simplify the fraction.
[tex]\[ x = -\frac{3}{5} \][/tex]
- Convert the fraction to a decimal.
[tex]\[ x = -0.6 \][/tex]
Therefore, the solution to the equation [tex]\(-4x - 2 = x + 1\)[/tex] is [tex]\(x = -0.6\)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.